Pre-extension Demonstration and Evaluation of Maize (Zea Mays l.) -Haricot Bean (Phaseolus Vulgaris l.) Intercropping Practices in Midlands of Guji Zone, Southern Oromia, Ethiopia - Girma Amare; Basha Kebede; Dembi Korji (International Journal of Scientific Multidisciplinary Research, 2024)
Intercropping is the simultaneous cultivation of two or more crops in both space and time. The activity was conducted during the main rainy season of 2019 in the Adola Rede and Odo Shakiso districts of Guji Zone, Oromia, Ethiopia. The demonstration Objectives includes evaluating yield output and cost-benefit ratio of maize-haricot bean intercropping practices under farmers’ condition and assessing farmers’ and others stakeholders’ preference on maize-haricot bean intercropping practices. Two Kebeles/sites per district were selected based on maize and haricot bean production potential. and 15 farmers were selected from each Kebele/site and grouped as one FRGs. Thus, a total of 4 FRGs comprising 60 farmers (45 male and 15 female) were established. Improved maize (BH-546) and haricot bean (Haramaya) varieties were demonstrated with sole cropping of respective maize and haricot bean on plots of 100 m2 area per variety at 40 cm inter- and 10 cm and 75 cm inter- and 25 cm intra row spacing for haricot bean and maize respectively, with recommended seed and fertilizer rates. Farmer-to-farmer learning on maize-haricot bean intercropping practices was enhanced through training, exchange visits, technology evaluation and field day. The data was collected using observation, measurement, face-to-face interviews, and the intercropping metrics. The collected data was analyzed using descriptive statistics, and farmers' preferences were analyzed qualitatively